Perceived barriers and facilitators towards help-seeking for eating disorders: a systematic review - Ali, Kathina; Bauer, Stephanie (The international journal of eating disorders, 2016)
OBJECTIVE: To systematically review the literature on perceived barriers and facilitators of help-seeking for eating disorders. METHOD: Three databases (PubMed, PsychInfo, Cochrane) were searched using keywords and Medical Subject Headings (MeSH) terms. Retrieved abstracts (N = 3493) were double screened and relevant papers (n = 13) were double coded. Qualitative and quantitative studies were included if they reported perceived barriers and facilitators towards seeking help for eating disorders. Barriers and facilitators were extracted from the included papers and coded under themes. The most prominent barriers and facilitators were determined by the number of studies reporting each theme. RESULTS: Eight qualitative, three quantitative, and two mixed-methods studies met the inclusion criteria for the current review. The most prominent perceived barriers to help-seeking were stigma and shame, denial of and failure to perceive the severity of the illness, practical barriers (e.g., cost of treatment), low motivation to change, negative attitudes towards seeking help, lack of encouragement from others to seek help and lack of knowledge about help resources. Facilitators of help-seeking were reported in six studies, with the most prominent themes identified as the presence of other mental health problems or emotional distress, and concerns about health. DISCUSSION: Programs targeting prevention and early intervention for eating disorders should focus on reducing stigma and shame, educating individuals about the severity of eating disorders, and increasing knowledge around help-seeking pathways for eating disorders.
Gesehen am 25.04.2018